The Effect of Vitamin-C Supply on Cardiorespiratory Endurance in Hockey Athletes - Syahruddin; Muhammad Ishak; Andi Ridwan; Sahabuddin Sahabuddin (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
This study is an experimental study aimed at determining the effect of vitamin C administration on cardiorespiratory endurance in UNM hockey athletes. The independent variable in this study is the administration of vitamin C, while the dependent variable is cardiorespiratory endurance. The population in this study were all male Hockey athletes of the Faculty of Sport Sciences, Makassar State University, while the sample was 14 male Hockey athletes from UNM. The data collection technique used was a multistage fitness test or bleep test. Data analysis used descriptive statistical analysis techniques and statistical analysis techniques. The results of descriptive statistics were obtained from the results of tests given to UNM hockey athletes. The results of statistical analysis by conducting hypothesis testing using the Paired Sample T-test on the post-test showed that the probability value = 0.007 so it was smaller than the significance level value of 5% (0.007 <0.05). The conclusion of this study shows that there is a significant effect of vitamin C administration on cardiorespiratory endurance in UNM hockey athletes.